Leadership styles & Frontline workers engagement in healthcare systems: A case of Australian Healthcare (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The paper explores the depth of association between diverse types of leadership and engagement and job satisfaction of frontline healthcare workers in the public healthcare system across Sydney, especially in the wake of the COVID-19 pandemic. The study aims to consider the crucial role of frontline personnel in relation to their public health setting, and gender-related responses to emergencies, especially in the context of the Australian healthcare system. The Study aimed at determining the existence of significant relationships within the leadership styles (transformational, transactional, laissez-faire, and democratic), perceived organizational support, the frontline healthcare staff engaged to work, and their job satisfaction. Also, the research was intended to provide a comparative analysis of the responses of male healthcare workers and female healthcare workers. A quantitative, cross-sectional survey approach was utilized, where the primary data were collected with the assistance of a structured questionnaire on Likert scales with 285 frontline healthcare workers in Sydney. Smart PLS-4 was used to conduct the analysis of the data obtained. The findings reveal that the perceived organizational support is the best positive predictor of the frontline healthcare worker engagement, exponentially accounting for 55.4 percent of its variance. In case of job satisfaction, with 72.6 percent of the total variance explained, laissez-faire and transformational leadership produced significant positive outcomes. Nonetheless, there is an indication of a possible discriminant validity problem based on the high values in the Heterotrait-Monotrait Ratio (HTMT) that indicates a possible problem with the relationship between transactional leadership and job satisfaction; hence, these relationships should be interpreted with care. The results also point to the great significance of a healthy organizational setting in encouraging engagement within the healthcare environment.